Analysis of Different Guide Elements’ Designs in Hydraulic Cylinders - Jan Pustavrh; Ana Trajkovski; Vito Tič; Marko Polajnar; Uroš Bohinc; Franc Majdič (Applied Sciences)
In this study, the frictional behaviours of three different guide elements—guide rings, labyrinth seals, and hydrostatic bearings—in hydraulic cylinders is investigated experimentally. A modular, double-acting hydraulic cylinder was designed to compare these three different design elements under different pressures (0 bar, 120 bar, and 240 bar), velocities, and radial loads. The results show that the guide rings exhibit the highest friction, especially at high pressures. Labyrinth seals exhibit significantly lower friction and extend the service life of the components. Hydrostatic bearings allow low friction but require precise control of the fluid, which limits their use. The results provide practical guidelines for selecting guide elements and optimising the friction performance, durability, and efficiency of hydraulic systems. We found that the best solution from the points of view of design, friction, and economics is to use labyrinth seals as guiding elements for the fast reciprocal moving rods of hydraulic cylinders.